Gambogenic acid induces apoptosis and autophagy through ROS‐mediated endoplasmic reticulum stress via JNK pathway in prostate cancer cells. (9th September 2022) - Wu, Jianjian; Wang, Dejuan; Zhou, Jiuyao; Li, Juntao; Xie, Ruoxin; Li, Yiyuan; Huang, Jiayu; Liu, Bihao; Qiu, Jianguang
Abstract: Prostate cancer (PCa) is the most common malignant tumor in males, which frequently develops into castration‐resistant prostate cancer (CRPC) with limited therapies. Gambogenic acid (GNA), a flavonoids compound isolated from Gamboge, exhibits anti‐tumor capacity in various cancers. Our results showed that GNA revealed not only antiproliferative and pro‐apoptotic activities but also the induction of autophagy in PCa cells. In addition, autophagy inhibitor chloroquine enhanced the pro‐apoptosis effect of GNA. Moreover, the activation of JNK pathway and the induction of apoptosis and autophagy triggered by GNA were attenuated by JNK inhibitor SP600125. We also found that GNA significantly promoted reactive oxygen species (ROS) generation and endoplasmic reticulum (ER) stress. Meanwhile, suppressing ER stress with 4‐phenylbutyric acid (4‐PBA) markedly blocked the activation of JNK pathway induced by GNA. Further research indicated that ROS scavenger N‐acetyl‐L‐cysteine (NAC) effectively abrogated ER stress and JNK pathway activation induced by GNA. Furthermore, NAC and 4‐PBA significantly reversed GNA‐triggered apoptosis and autophagy. Finally, GNA remarkably suppressed prostate tumor growth with low toxicity in vivo. In conclusion, the present study revealed that GNA induced apoptosis and autophagy through ROS‐mediated ER stress via JNK signaling pathway in PCa cells. Thus, GNA might be a promising therapeutic drug against PCa.